1992
DOI: 10.2337/diab.41.12.1570
|View full text |Cite
|
Sign up to set email alerts
|

Improved Specificity of ICA Assays in the Fourth International Immunology of Diabetes Serum Exchange Workshop

Abstract: The goal of the Fourth International Workshop for Standardization of ICA Measurements was to determine the specificity of ICA assays and their ability to distinguish between control sera (n = 57) and sera from IDDM-related individuals--representing relatives of IDDM patients (n = 21), healthy individuals who later developed IDDM (n = 8), or newly diagnosed IDDM patients (n = 23). Results from 28 laboratories were analyzed. The mean specificity (percentage of control sera reported as negative) among 27 laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 16 publications
(20 reference statements)
0
54
0
Order By: Relevance
“…On the other hand, one should bear in mind that the limitations of ICA assay are the demanding standardization and challenging interpretation of the results. Despite those restrictions, in the 4 th International ICA Workshop it was reported that ICA diagnostic test has exceptional specificity and acceptable concordance among the different laboratories [21] . There is a bunch of studies addressing the ICAs relevance to T1D.…”
Section: Immunological Characteristicsmentioning
confidence: 99%
“…On the other hand, one should bear in mind that the limitations of ICA assay are the demanding standardization and challenging interpretation of the results. Despite those restrictions, in the 4 th International ICA Workshop it was reported that ICA diagnostic test has exceptional specificity and acceptable concordance among the different laboratories [21] . There is a bunch of studies addressing the ICAs relevance to T1D.…”
Section: Immunological Characteristicsmentioning
confidence: 99%
“…Our laboratory participated in the 13 th Immunology of Diabetes Workshop Standardization and showed 100% sensitivity and specificity. Levels of ICA are expressed in Juvenile Diabetes Foundation Units ( JDF-U), using the world reference standard curve based on the international JDF reference sera (14).…”
Section: Radiobinding Assay (Rba) Of Ljungan Virus Antibodies (Lvabmentioning
confidence: 99%
“…These diagnostic and predictive abilities did not naturally present themselves, as much of the early literature regarding autoantibodies in type 1 diabetes was subject to controversies and conflicting information-factors due in large part to variances in the methods and substrates used for autoantibody detection. Considerable advances toward overcoming these difficulties came through the voluntary performance of many investigators in more than a dozen international autoantibody workshops, often organized under the auspices of the Immunology of Diabetes Workshops, an organization that later became known as the Immunology of Diabetes Society (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Among their many findings, these workshops validated insulin, GAD, and IA-2 as autoantigens associated with type 1 diabetes in humans; identified sensitive and specific methods for autoantibody measurement; and introduced reference standards for diabetesassociated autoantibodies.…”
mentioning
confidence: 99%